Pharmacogenetic algorithm for predicting daily dose of warfarin in Caucasian patients of Czech origin - Tomek, Aleš; Růžičková, Tereza; Kaplan, Vojtěch; Lacinová, Zuzana; Kumstýřová, Simona; Šrámek, Martin; Olšerová, Anna; Janský, Petr; Kolářová, Tereza; Neumann, Jiří; Schwabová, Jaroslava Paulasová; Maťoška, Václav (Drug metabolism and personalized therapy, 2020)
OBJECTIVES: Warfarin use is limited by a low therapeutic index and significant interindividual variability of the daily dose. The most important factor predicting daily warfarin dose is individual genotype, polymorphisms of genes CYP2C9 (warfarin metabolism) and VKORC1 (sensitivity for warfarin). Algorithms using clinical and genetic variables could predict the daily dose before the initiation of therapy. The aim of this study was to develop and validate an algorithm for the prediction of warfarin daily dose in Czech patients. METHODS: Detailed clinical data of patients with known and stable warfarin daily dose were collected. All patients were genotyped for polymorphisms in genes CYP2C9 and VKORC1. RESULTS: Included patients were divided into derivation (n=175) and validation (n=223) cohorts. The final algorithm includes the following variables: Age, height, weight, treatment with amiodarone and presence of variant alleles of genes CYP2C9 and VKORC1. The adjusted coefficient of determination is 72.4% in the derivation and 62.3% in the validation cohort (p<0.001). CONCLUSIONS: Our validated algorithm for warfarin daily dose prediction in our Czech cohort had higher precision than other currently published algorithms. Pharmacogenetics of warfarin has the potential in the clinical practice in specialized centers.
Keywords: VKORC1; warfarin; pharmacogenetics; daily dose prediction algorithm; CYP2C9